Revealing the Hypoglycemic Effects and Mechanism of GABA-Rich Germinated Adzuki Beans on T2DM Mice by Untargeted Serum Metabolomics - Jiang, Xiujie; Xu, Qingpeng; Zhang, Aiwu; Liu, Yong; Li, Zhijiang; Tang, Huacheng; Cao, Dongmei; Zhang, Dongjie (Frontiers in Nutrition, 2021)
Type 2 diabetes mellitus(T2DM) is one of the most common metabolic disease, exploring the strategies of preventing and treating diabetes are extremely importan.Therefore, looking for new dietary intervention therapeutic strategy for T2DM has attracted more public attentions.This study aimed to elucidate the effects and the possible mechanisms of different dosages of GABA-rich germinated adzuki beans on the treatment of diabetes mice. Establish diabetic model with C57BL/6J mice by high-fat diet (HFD) feeding combining with injection of low-dose streptozotocin (STZ),and treated for six weeks, separately with TF1,TF2,TF3,B,TG and the positive control drug metformin(TS).Then, detected blood glucose level and blood lipid biochemical indicators of all mice.Simultaneously, the Serum differential metabolite interactions were explored by UPLC-Q/TOF-MS-based serum metabolomic analysis.The results showed that the WB and FBG levels were significantly reduced (p < 0.05),which also recovered levels of TC,TG, AST,ALT, Ure and Serum creatinine,and significantly promoted HOMA-β and INS indexs(p < 0.05) , reduced insulin resistance indexes(p < 0.05) in the TF3 group.In addition, the metabolic profiles of serum were analyzed and obtained 31 differential metabolites including amino acids and lipids. According to KEGG pathway enrichment analysis,found to be correlated with 9 significantly metabolic pathways involving the up-regulation of the levels of L-serine,SM(d18:1/22:1(13Z)),L-histidine,creatine and 3-indoleacetic acid.It is suggested that the hypoglycemic effect of GABA-rich germinated adzuki beans on diabetic mice may be related to improving tryptophan metabolism, glycerol phospholipin metabolism, sphingol metabolism, glycine, serine, and threonine metabolic pathways.This study will be provide reference to the application of GABA-enriched germinate foods in type 2 diabetes and could provide a cue for searching biomarkers of the T2DM diagnosis.